Development of Learning Games toward Informatics Subjects in Class VII SMP - Febriyenti, Frety; Hidayati, Abna (JUPE : Jurnal Pendidikan Mandala, 2023)
This research is motivated by several facts found in the field. Students still find it difficult to understand some of the Informatics subject matter because the material is quite complex. This is because apart from the material being quite difficult to understand, the Informatics subject is new for class VII students. Problems related to students not understanding the material at SMP Negeri 15 Padang class VII are caused by monotonous learning and teachers rarely use learning media during learning activities. This research aims to produce learning game media for class VII junior high school Informatics subjects that are valid, practical and effective. This type of research is development research, known as Research and Development (R&D), using the 4-D development model. The development procedure in this research consists of 4 stages, namely; (1) Define, (2) Design, (3) Develop, (4) Disseminate. The product validity test was carried out by 3 validators, namely 1 material validator and 2 media validators. Product trials were carried out on 31 class VII students of SMP Negeri 15 Padang with the aim of finding out the practicality and effectiveness of the product being developed. The development of this learning game media has been validated by 1 material expert and 2 media experts, whose respective assessment results have been categorized as "Very Valid" with an average score of 98.35% for the material, and 97.98% for the media used. went through 2 validation stages with several revisions to the media. The results of practicality trials in the field obtained a score of 98.12%, so that the learning game media is in the "Very Practical" category. Based on the results of the validity test, and practicality test, it can be concluded that the resulting learning media is suitable and can be used in Informatics subjects for class VII SMP.